대장균 기반 인슐린 유사 성장인자-I 검출용 퀜치바디 생산 - 유정수; 이준엽; 정재훈; 정희진; 양영헌; 손정현; 성창민 (한국생물공학회, 2023)
A recombinant human growth hormone (rhGH) was developed as a prescription drug to treat growth disorders and growth hormone deficiency, but it has been abused for the purpose of doping to improve physical performance by athletes. The World Anti-Doping Agency (WADA) has listed it as a prohibited substances, and has published guidelines for GH isoform and GH biomarker analysis to detect growth hormone doping. General detection mathod for Insulin-like growth factor-I (IGF-I), one of the GH biomarkers, is immunoradiometric assay and mass spectrometry. However, these methods have disadvantages such as the risk of radioactivity, high cost, and long analysis time. In this study, we tried to develop a fluorescent antibody sensor called Quenchbody for rapid detection of IGF-I in the process of growth hormone doping test. A vector was designed in consideration of codon optimization and purification for the anti-hIGF-I scFv sequence for E. coli production, and this was transformed to prepare an anti-hIGFI scFv-producing strain. The expressed antibody was purified using His-tag and Flag-tag, and a Quenchbody was finally produced through fluorescent dye labeling through maleimide- thiol reaction. The antigen binding activity of the Quenchbody were confirmed by ELISA and fluorescence signal detection according to the antigen concentration, and the detection limit of the ATTO520-labeled anti-hIGF-I scFv was 120 pM and the quantitation limit was 540 pM. The IGF-I detection method using a 96-well plate-based Quenchbody is possible from sample preparation to detection within 30 minutes, and is expected to be able to process a large amount of samples.